Design Interactive Book of The Tanah Airku Theme for Early Childhood with Art-Base in Semarang District - Henti Desyta Utomo; Birmanti Setia Utami; Peni Pratiwi Pratiwi (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
AbstractNationalism education in this globalization era is a form of filterization for children to maintain national identity and culture. The National insight in the 2013 PAUD curriculum is contained in the theme of my homeland. The problem is the lack of teaching materials for the homeland theme caused the lack of teacher creativity. The teaching materials consist of interactive book for children and manual/ guide book for teacher/ facilitator using an artwork base according to the Waldorf learning models. The research subject of children aged 4-6 years amounted to 20 children. This research uses a mix method. The results showed the validity and data gained from 80% expert materials, media experts 82.2%, and a 82.5% teacher response entered in a very good category. The results of the feasibility test of 20 students showed that the student’s interest was very high in the resulting interactive book. Based on the results of interviews with the teacher showed that students seemed more enthusiastic and enthusiastic in learning so that the activity in the class also increased. Based on the results of the validation of the material experts, media experts, teachers, and student responses that on average show a good category. Then the interactive book media theme of my homeland can be used as a learning tool in an interesting way and in accordance with the development and abilities of students.Keywords: Interactive Book; Early Childhood; Teaching Materials; Homeland; Artwork. Abstrak Pendidikan wawasan kebangsaan pada era globalisasi ini merupakan bentuk filterisasi bagi anak-anak untuk mempertahankan identitas dan budaya bangsa. Wawasan kebangsaan dalam Kurikulum PAUD 2013 termuat dalam tema tanah airku. Permasalahan yang ada adalah minimnya bahan ajar untuk tema tanah air disebabkan kurangnya kreativitas guru. Karya perancangan bahan ajar berupa buku interaktif untuk anak dan buku panduan untuk guru/ pendamping yang dirancang menggunakan basis karya seni sesuai dengan model pembelajaran Waldorf. Subjek penelitian anak usia 4-6 tahun berjumlah 20 anak. Penelitian ini menggunakan metode campuran. Hasil dari penelitian menunjukan kevalidan data yang diperoleh dari ahli materi 80%, ahli media 82,2%, dan respon guru 82,5% masuk dalam kategori sangat baik. Hasil pengujian kelayakan terhadap 20 siswa menunjukkan ketertarikan siswa terhadap buku interaktif yang dihasilkan sangat tinggi. Berdasarkan hasil wawancara dengan guru menunjukkan bahwa siswa tampak lebih bersemangat dan antusias dalam belajar sehingga keaktifan di kelaspun meningkat. Berdasarkan hasil validasi ahli materi, ahli media, guru, dan respon siswa yang rata-rata menunjukkan kategori baik. Maka media buku interaktif tema tanah airku dapat digunakan sebagai sarana belajar dengan cara yang menarik dan sesuai dengan perkembangan dan kemampuan siswa. Kata Kunci: Buku Interaktif; Anak Usia Dini; Bahan Ajar; Tanah Air; Karya Seni.